Pengembangan Ensiklopedia Terintegrasi Potensi Lokal Sumatera Utara Tumbuhan Balakka (Phyllanthus emblica L) sebagai Alternatif Bahan Ajar Biologi - Luthfiah Ananda; Indayana Febriani Tanjung; Irwan Syahputra (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This research aims to determine the feasibility, practicality, and effectiveness of the encyclopedia developed on Kingdom Plantae (Plant Kingdom) material. The method used in this research is the Research and Development (R&D) method with the 4D model (Define, Design, Development, and Disseminate) from Thiagarajan. The research results show that the Encyclopedia is very feasible, practical, and effective to be used as open material for SMA/MA students. This is seen based on the assessment of experts by material experts with a percentage of 80%, media experts with a percentage of 90.9%, biology subject teachers with a percentage of 75%, practicality by students with a percentage of 90.4%, and product effectiveness seen from the Learning Completeness formula with a percentage amounting to 87.30%. Encyclopedias that are suitable for development will then be distributed to several schools, namely MAS Al-Ulum Medan and SMAS Nur Ihsan Islamic Fullday School. Keywords: Kingdom Plantae Encyclopedia, Thiagarajan 4D Model